The microbiome and cytosolic innate immune receptors. Issue 1 (13th July 2020) - Liwinski, Timur; Zheng, Danping; Elinav, Eran
Abstract: The discovery of innate immune sensors (pattern recognition receptors, PRRs) has profoundly transformed the notion of innate immunity, in providing a mechanistic basis for host immune interactions with a wealth of environmental signals, leading to a variety of immune‐mediated outcomes including instruction and activation of the adaptive immune arm. As part of this growing understanding of host‐environmental cross talk, an intimate connection has been unveiled between innate immune sensors and signals perceived from the commensal microbiota, which may be regarded as a hub integrating a variety of environmental cues. Among cytosolic PRRs impacting on host homeostasis by interacting with the commensal microbiota are nucleotide‐binding domain, leucine‐rich repeat‐containing protein receptors (NLRs), together with a number of cytosolic DNA sensors and the family of absent in melanoma (AIM)–like receptors (ALRs). NLR sensors have been a particular focus of research, and some NLRs have emerged as key orchestrators of inflammatory responses and host homeostasis. Some NLRs achieve this through the formation of cytoplasmic multiprotein complexes termed inflammasomes. More recently discovered PRRs include retinoic acid‐inducible gene‐I (RIG‐I)–like receptors (RLRs), cyclic GMP‐AMP synthase (cGAS), and STING. In the present review, they summarize recent advancements in knowledge on structure and function of cytosolic PRRs and their roles in host‐microbiota cross talk and immune surveillance. In addition, we discuss their relevance for human health and disease and future therapeutic applications involving modulation of their activation and signaling.